MiR-219a-5p Enriched Extracellular Vesicles Induce OPC Differentiation and EAE Improvement More Efficiently Than Liposomes and Polymeric Nanoparticles - Iñaki Osorio-Querejeta; Susana Carregal-Romero; Ana Ayerdi-Izquierdo; Imre Mäger; Leslie A. Nash; Matthew Wood; Ander Egimendia; M. Betanzos; Ainhoa Alberro; Leire Iparraguirre; Laura Moles; Irantzu Llarena; et al. (MDPI AG, 2020)
Remyelination is a key aspect in multiple sclerosis pathology and a special effort is being made to promote it. However, there is still no available treatment to regenerate myelin and several strategies are being scrutinized. Myelination is naturally performed by oligodendrocytes and microRNAs have been postulated as a promising tool to induce oligodendrocyte precursor cell differentiation and therefore remyelination. Herein, DSPC liposomes and PLGA nanoparticles were studied for miR-219a-5p encapsulation, release and remyelination promotion. In parallel, they were compared with biologically engineered extracellular vesicles overexpressing miR-219a-5p. Interestingly, extracellular vesicles showed the highest oligodendrocyte precursor cell differentiation levels and were more effective than liposomes and polymeric nanoparticles crossing the blood−brain barrier. Finally, extracellular vesicles were able to improve EAE animal model clinical evolution. Our results indicate that the use of extracellular vesicles as miR-219a-5p delivery system can be a feasible and promising strategy to induce remyelination in multiple sclerosis patients.